Nature-Based Relaxation Videos and Their Effect on Heart Rate Variability - Benz, Annika B. E.; Gaertner, Raphaela J.; Meier, Maria; Unternaehrer, Eva; Scharndke, Simona; Jupe, Clara; Wenzel, Maya; Bentele, Ulrike U.; Dimitroff, Stephanie J.; Denk, Bernadette F.; Pruessner, Jens C. (Frontiers in Psychology, 2022)
Growing evidence suggests that natural environments – whether in outdoor or indoor settings – foster psychological health and physiological relaxation, indicated by increased well-being, reduced stress levels, and increased parasympathetic activity. Greater insight into differential psychological aspects modulating psychophysiological responses to nature-based relaxation videos could help understand modes of action and develop personalized relaxation interventions. We investigated heart rate variability (HRV) as an indicator of autonomic regulation, specifically parasympathetic activity, in response to a 10-minute video intervention in two consecutive studies as well as heart rate (HR). We hypothesized that a nature-based relaxation video elicits HRV increase and HR decrease, with response magnitude being affected by aspects of early life adversity (conceptualized as low parental care and high overprotection/constraint) and trait mindfulness. In Study 1, N=60 participants (52% female, agemean=23.92±3.13 years, agerange=18–34 years) watched a relaxation video intervention depicting different natural scenery. We analyzed changes in HR and respiratory sinus arrhythmia (RSA) as a standard HRV measure, both based on 3-minute segments from the experimental session, in multiple growth curve models. We found a decrease in HR and increase of RSA during the video intervention. Higher paternal care and lower trait mindfulness observing skills (assessed via questionnaires) were associated with higher RSA values before but not during video exposure. In Study 2, N=90 participants (50% female, age: mean=22.63±4.57 years, range=18–49 years) were assigned to three video conditions: natural scenery from Study 1, meditation video, or short clip from “The Lord of the Rings”. Again, HR decreased, and RSA increased during video segments, yet without expected group differences across different video types. We found higher parental care and lower parental overprotection to predict higher RSA at different times during the experiment. Interestingly, lower paternal overprotection predicted overall higher RSA. These results suggest a generic relaxation effect of video interventions on autonomic regulation that we discuss in light of different theories mapping restorative effects of natural environments. Further, psychological characteristics like aspects of early life adversity and trait mindfulness could contribute to individual differences in autonomic regulation. This study contributes to a better understanding of autonomic and psychological responses to relaxation videos.